THE USE OF SMARTWATCH DEVICES IN SCREENING FOR CARDIAC ARRHYTHMIAS: A NARRATIVE REVIEW OF CURRENT CAPABILITIES AND LIMITATIONS - Aleksandra Gralec; Piotr Helbin; Katarzyna Szlachetka; Piotr Tryczyński; Jakub Wrona; Jakub Sałak; Wiktoria Donocik (International Journal of Innovative Technologies in Social Science, 2026)
Background: Atrial fibrillation (AF) is a major stroke risk, yet its asymptomatic nature complicates early detection. While smartwatches using photoplethysmography (PPG) and electrocardiogram (ECG) sensors offer continuous monitoring, their mass adoption introduces profound socio-technological and psychological challenges. Objective: This review evaluates the diagnostic accuracy of consumer wearables against clinical standards, specifically emphasizing their broader societal impacts, including digital health inequity, algorithmic bias, and technology-induced health anxiety. Methods: We analyzed literature from PubMed and Google Scholar (2007–2026), reviewing major population trials (e.g., Apple, Huawei, and Fitbit Heart Studies) alongside current guidelines from major cardiovascular societies (ESC, EHRA). Results: Although resting PPG sensors demonstrate high sensitivity (>90%) and specificity (>95%) for AF detection, real-world accuracy frequently decreases due to motion artifacts, advanced age, and darker skin tones. This algorithmic bias creates a tangible risk of digital health exclusion. Furthermore, continuous biometric tracking often triggers "cyberchondria" and burdens healthcare systems with asymptomatic, low-risk patients (the "worried well"). Additionally, industry-funded trials may overstate clinical benefits to drive commercial sales. Conclusion: Smartwatches represent a significant advancement in preventative healthcare. However, due to inherent demographic biases and psychological risks, they must serve strictly as preliminary screening tools rather than definitive diagnostics. Prioritizing digital equity, patient well-being, and independent physician oversight is crucial for integrating these devices safely into modern society.